2020
DOI: 10.3389/ffgc.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

No Net Loss of Species Diversity After Prescribed Fires in the Brazilian Savanna

Abstract: Although savannas are fire-adapted ecosystems, prescribing fire for biodiversity conservation remains controversial at least in some regions where savannas occur. Faced with uncertainty, many decision makers and even scientists are still reluctant to prescribe fire for conservation purposes in fire-prone ecosystems, invoking the precautionary principle. Knowledge gaps on the ideal fire regime, such as how and when to burn, and especially the fear of biodiversity losses, are among the main arguments against fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 128 publications
4
32
0
7
Order By: Relevance
“…Biodiversity was not significantly affected by fire across any taxa group, climate type, or time since fire, indicating an overall high resilience at the analyzed spatial and temporal scales. This is in line with previous studies focused on specific semiarid regions, including two wellstudied large fire-prone ecosystems in South America (i.e., Cerrado and the Gran Chaco), which had shown post-fire recovery of biodiversity for different taxa groups, such as plants, birds, and insects (e.g., Kunst et al 2003Kunst et al , 2015Kowaljow et al 2019;Durigan et al 2020;Pilon et al 2021). However, these responses may certainly involve context-dependent changes in species composition (Durigan et al 2020;McLauchlan et al 2020), which could not be captured in our quantitative synthesis.…”
Section: Effect Of Fire On the Response Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…Biodiversity was not significantly affected by fire across any taxa group, climate type, or time since fire, indicating an overall high resilience at the analyzed spatial and temporal scales. This is in line with previous studies focused on specific semiarid regions, including two wellstudied large fire-prone ecosystems in South America (i.e., Cerrado and the Gran Chaco), which had shown post-fire recovery of biodiversity for different taxa groups, such as plants, birds, and insects (e.g., Kunst et al 2003Kunst et al , 2015Kowaljow et al 2019;Durigan et al 2020;Pilon et al 2021). However, these responses may certainly involve context-dependent changes in species composition (Durigan et al 2020;McLauchlan et al 2020), which could not be captured in our quantitative synthesis.…”
Section: Effect Of Fire On the Response Variablessupporting
confidence: 89%
“…6C). The early vegetative response reflects the high resprouting capacity of many shrub species across the studied regions, especially in fire-prone regions (Gurvich et al 2005;Bravo et al 2014;Torres et al 2014;Durigan et al 2020;Jaureguiberry et al 2020). Regarding the reproductive response, the pattern reported here agrees with previous evidence suggesting that shrubs might reach minimum reproductive sizes soon after fire, then slow down their growth rate and reproduction as succession progresses (Hoffmann and Moreira 2002;Hoffmann and Solbrig 2003;Galíndez et al 2009).…”
Section: Effect Of Fire On the Response Variablessupporting
confidence: 86%
“…A study of bird responses to a large fire elsewhere in Kruger found that species richness and composition did not vary with fire intensity, and it was concluded that bird communities are likely to be robust to all but the most extreme fire regimes (Mills, 2004). The Brazilian savanna fauna is likewise highly resilient to fire (Durigan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, biennial fires negatively affect tree and shrub biomass, on the other hand herbs and grasses need to be managed with fire in order to maintain the biodiversity and functioning of the ecosystem (Pinheiro and Durigan, 2009;Abreu et al, 2017;Durigan et al, 2020). As such, we suggest the use of prescribed burns in mosaic configurations with different fire frequencies (no fire and quadrennial fires).…”
Section: Discussionmentioning
confidence: 99%